Peridural analgesia does not impact survival in patients after colon cancer resection: a retrospective propensity score-adjusted analysis - Wurster, Elena Felicia; Pianka, Frank; Warschkow, René; Antony, Pia-Anita; Brenner, Thorsten; Weigand, Markus A.; Schmied, Bruno; Büchler, Markus W.; Tarantino, Ignazio; Ulrich, Alexis (International journal of colorectal disease, 2019)
PurposeTo assess the putative impact of peridural analgesia on oncological outcome in patients undergoing resection of stages I-IV colon cancer.MethodsIn a single-center study, 876 patients undergoing resection for primary colon cancer (AJCC stages I-IV) between 2001 and 2014 were analyzed. Mean follow-up of the entire cohort was 4.2 ± 3.5 years. Patients who did and did not receive peridural analgesia were compared using Cox regression and propensity score analyses.ResultsOverall, 208 patients (23.7%) received peridural analgesia. Patients’ characteristics were biased with regard to the use of peridural analgesia (propensity score 0.296 ± 0.129 vs. 0.219 ± 0.108, p < 0.001). After propensity score matching, the use of peridural analgesia had no impact on overall (HR 0.81, 95% CI 0.59-1.11, p = 0.175), cancer-specific (HR 0.72, 95% CI 0.48-1.09, p = 0.111), and disease-free survival (HR 0.89, 95% CI 0.66-1.19, p = 0.430). The 5-year overall survival after propensity score matching was 60.9% (95% CI 54.8-67.7%) for patients treated with peridural analgesia compared with 54.1% (95% CI 49.5-59.1%) for patients not treated with peridural analgesia. Cancer-specific and disease-free survival showed similar non-significant results.ConclusionsPeridural analgesia in patients after colon cancer resection was not associated with a better oncological outcome after risk adjusting in multivariable Cox regression and propensity score analyses. Hence, oncological outcome should not serve as a reason for the use of peridural analgesia in patients with colon cancer.
Published online: 6 June 2019
Gesehen am 02.10.2019